Oilfield Chemistry - Dai, Caili (Springer Singapore, 2018)
This book provides comprehensive information on the youngest member of the petroleum sciences family: Oilfield Chemistry, proposes the chemical agents for addressing current problems, and explains the functions, mechanisms and synergistic effects of various chemical agents.